Ischemia modified albumin (IMA) and albumin adjusted-IMA (AAIMA) as biomarkers for diabetic retinopathy - Reddy, Varikasuvu Seshadri; Sethi, Sumita; Agrawal, Poonam; Gupta, Navdeep; Garg, Renu (Nepalese Journal of Ophthalmology, 2016)
Introduction: Oxidative stress has important role in the pathophysiology of diabetic retinopathy (DR). Ischemia modified albumin (IMA) has been recently considered as a marker of oxidative damage in diabetes. However, there is scarcity of published information about both IMA and albumin adjusted-IMA (AAIMA) in DR patients. Objectives: To evaluate the serum levels of IMA and AAIMA in patients with DR and in healthy controls. Material and methods: This was a cross sectional study. Serum was obtained to measure lipids, albumin and IMA from the the patients with DR and non-diabetic subjects. The IMA level was measured by a colorimetric albumin cobalt binding (ACB) assay and the values were presented as absorbance units (ABSU). The IMA levels were adjusted for albumin interference and the AAIMA by using a formula [Individual serum albumin/median albumin concentration of the population X IMA]. Results: This study was done on 18 DR and 20 non- diabetic patients. The mean Serum IMA values in DR group and controls were 0.50±0.17 and 0.32±0.17, respectively (P=0.002). The mean serum AAIMA values in DR group and controls were 0.48±0.20 and 0.32±0.17, respectively (P=0.01). The albumin and HDL- Cholesterol levels were significantly lower in DR patients compared to controls (p=0.004 and p=0.01, respectively). Conclusions: The level of IMA and AAIMA were higher in cases of DR compared to that of non-diabetic subjects. The levels of albumin and HDL-Cholesterol were lower in DR patients compared to controls.